The influence of socio-economic factors on behavioral intention to use mobile phones among fishermen in Pangkor Island - Mazuki R.; Omar S.Z.; Bolong J.; D'Silva J.L.; Hassan M.A.; Shaffril H.A.M. (2024)
Indexed by Scopus